PARADIGMA ETIS-REGULATIF DALAM KEBIJAKAN HIV/AIDS STUDI ANALISIS TERHADAP PERMENKES NO. 23 TAHUN 2022 - Habibah Zulaiha; Emilatantri Ningsih; Mansia Khafifah (Yayasan Baitul Hikmah al-Zain, 2025)
HIV/AIDS control policies in Indonesia have shifted from a purely medical response to a multidimensional approach that encompasses legal, ethical, and social justice aspects. Minister of Health Regulation (Permenkes) No. 23 of 2022 is the latest regulation that reaffirms the state's commitment to comprehensive HIV/AIDS control. This article aims to analyze the Permenkes from an ethical-regulatory perspective, focusing on how legal norms and ethical values are constructed within public health policy. The study employs a qualitative approach using document analysis and normative-philosophical analysis of the regulation's content, in relation to principles of health ethics such as non-maleficence, justice, autonomy, and beneficence. The analysis shows that Permenkes No. 23/2022 has normatively accommodated public ethical principles, such as confidentiality protection, the right to treatment, and the prevention of stigma and discrimination. However, implementation in the field still faces structural challenges, including service limitations, regional disparities, and social resistance. This article recommends the need for stronger integration between legal and ethical-participatory approaches in policy implementation, so that HIV/AIDS prevention is not only effective in regulatory terms but also morally just.